Pyosalpinx as a sequela of labial fusion in a post-menopausal woman: a case report - Tsianos, Georgios I.; Papatheodorou, Stefania; Michos, George M.; Koliopoulos, George; Stefos, Theodor I. (My University, 2011)
Introduction. Complete labia fusion is a rare clinical entity in post-menopausal women. The most common complications of this presentation are infections of the urinary tract and retention of urine in the vagina. We present the case of a post-menopausal woman with adnexal mass and abdominal pain due to fusion of the labia majora. To the best of our knowledge this is the first report in the literature of this complication. Case presentation. A 78-year-old Caucasian woman was admitted to our hospital due to abdominal pain and urination difficulty, along with fever and leucocytosis. On examination the labial majora were fused. Computed tomography of the abdomen revealed a cystic formation in the anatomical area of the right adnexa. Our patient had developed a pyosalpinx as a Sequela of labial fusion. At laparoscopy the right pyosalpinx was identified and resected, whereas the labia majora were reconstructed via dissection and separation. Conclusions: Labial fusion is a rare clinical entity in post-menopausal women and can have serious and unexpected complications. Though this presentation is rare, a clinical examination must be performed in detail in order to gain valuable information for an accurate diagnosis. Post-operational instruction must be given to patients in order to prevent the re-occurrence of the fusion and its complications.
Keywords: Fallopian Tube; Bacterial Vaginosis; Chlamydia Trachomatis; Pelvic Inflammatory Disease; Lichen Sclerosus